PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHINGAND LEARNING (CTL)BERBANTU MEDIA GAMBARTERHADAPHASIL BELAJAR,KINERJA GURU DAN AKTIVITAS SISWA IPS SEMESTER 2 KELAS VI SDNEGERI 1 BUGO JEPARA - Singgih Adhi P; Lynda Puspita Sari (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
This research is motivated by low yields and social studies teachers do not use the model of learning in learning. The problem in this research is "Is there any application of learning models CTL assisted Media Images on learning outcomes, teacher performance and student activity IPS sixth grade students of SD Negeri 1 Bugo Jepara?". This study aims to determine the application of learning models CTL assisted Media Images on learning outcomes, teacher performance and student activity IPS sixth grade students of SD Negeri 1 Bugo Jepara. Results showed hypothesis test obtained thitung price ttabel 1.685 5.862 thus thitung> ttable or 5.862> 1.685, the then Ho is rejected and H1 accepted or it can be said that the average difference in initial conditions with final conditions significantly. The conclusion was that no application of learning models CTL assisted Media Image Of Learning Outcomes IPS Grade VI Elementary School 1 Bugo Jepara. Keywords: Contextual Teaching and Learning (CTL), Media Image, IPS Learning Outcomes, Performance Teacher, Student Activities